ANÁLISE DO PERFIL DE USUÁRIOS QUE ACESSARAM O SERVIÇO DE EMERGÊNCIA DE UM HOSPITAL GERAL - ALVAREZ, CLAUDIA V.; STUMM, ENIVA M. F.; HILDEBRANDT, LEILA M.; STUMM, LILIAN K. (Salão do Conhecimento, 2013)
Resumo